Situation of Vaccine Research and Development in Thailand in 2008 - ลิ้มวัฒนายิ่งยง อรรถยา; ศิริพิทยาคุณกิจ อัญชลี; เปรมศรี นคร; เตชะธวัช ศิริรัตน์; เมืองชนะ จรุง (Disease Control Journal, 2009)
This descriptive study was conducted to review the current situation of vaccine research and development in Thailand. It was designed to study visit the research organizations and their supporting unit. There were 6 related organizations. (Center for Vaccine Development, Faculty of Medicine Siriraj Hospital, Medical Biotechnology Center, National Center for Genetic Engineering and Biotechnology, Vaccine Trial Center, National Laboratory Animal Center). It was found that the potential of the research organizations was modest. There were many vaccines developed to prevent communicable diseases which were the major public health problems with appropriate technology. (Dengue vaccine, JE vaccine, HIV vaccine, Influenza and Avian influenza vaccine) But no vaccine against malaria, leptospirosis were developed, nor could be expected in the recent future. The new technologies such as genetic engineering were required for future projection. In clinical level, many clinical trials in Thailand were conducted in accordance with Good Clinical Practice. In contrast, the preclinical studies were lack of expertise in managing researches to meet Good Laboratory Practice standard. The infrastructures included standard laboratories and pilot plant were also available. The human resources and training, funding and animal models especially primate and ferret were not sufficient. The most important things which was urgently necessary was how to fill the gaps between preclinical, clinical and industrial process development. There were some co-operation between local and regional organizations, but national and international partnership still to develop. National vaccine policy was established and set the priority of necessary vaccines. But the policy had not well recognized and implementation. In conclusion, vaccine development in Thailand were not well developed. The essential elements of success were the development of potential and infrastructures of research and development, the authorized organization for driving the policy and research co-operation. These key factors were crucial for Thailand long term vaccine self reliance.